2023
DOI: 10.3389/fendo.2023.1130791
|View full text |Cite
|
Sign up to set email alerts
|

En bloc resection of total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach in papillary thyroid carcinoma

Abstract: IntroductionThe current study presents a preliminary exploration of en bloc resection via a gasless transoral approach in papillary thyroid carcinoma.ObjectiveThis study aimed to summarize and explore the efficacy and safety of en bloc resection of total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach in patients with papillary thyroid carcinoma.MethodsThis study was conducted between January 2021 and December 2021. It involved 30 patients with bilateral papillary thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…En-bloc resection is an appropriate approach aligned with the oncologic concept ( 8 ) and has been practiced in thyroid surgery at our institution since January 2010 ( 25 ). Our current study revealed a notable increase in the number of lymph nodes obtained in the modified en-bloc group (7.5 ± 4.5) compared to the conventional group (5.6 ± 3.6) (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En-bloc resection is an appropriate approach aligned with the oncologic concept ( 8 ) and has been practiced in thyroid surgery at our institution since January 2010 ( 25 ). Our current study revealed a notable increase in the number of lymph nodes obtained in the modified en-bloc group (7.5 ± 4.5) compared to the conventional group (5.6 ± 3.6) (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…(7) Complete the en-bloc resection of the thyroid and central compartment and save the superior parathyroid gland by cutting close by the thyroid capsule. (8) Resect the posterior lymph nodes around the recurrent laryngeal nerve when necessary (Supplementary Video 1).…”
Section: Steps Of Modified En-bloc Resectionmentioning
confidence: 99%
See 1 more Smart Citation